2020
DOI: 10.1002/cad.20326
|View full text |Cite
|
Sign up to set email alerts
|

Twice Exceptional Students: Gifts and Talents, the Performing Arts, and Juvenile Delinquency

Abstract: There is an increasing attention to the phenomenon referred to as “twice exceptional” (“2e”) children, namely, children who demonstrate both exceptional abilities and disabilities. In this essay, this concept is applied to delinquency and/or emotional‐behavior disorder and gifts (talents) in the performance arts, exploring the presence of this association and the support for it in the literature. The essay asserts that this association does exist, qualifies these youth as another category of 2e students, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…A national evaluation of arts-based programs in the US, which involved participatory arts such as drama, photography, and dance, provided preliminary evidence that they reduced reportedly antisocial or criminalized behavior (Clawson & Coolbaugh, 2001 ). In these arts programs, adolescents may gain opportunities to improve their communication skills, self-confidence (Hughes, 2005 ), problem-solving skills, sense of purpose and autonomy, and social competence (Grigorenko, 2020 ), as well as finding new ways for positive self-expression (Gussak & Ploumis-Devick, 2004 ). The arts may thus have an important role in changing the individual, institutional, and social circumstances that can lead to reportedly antisocial or criminalized behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A national evaluation of arts-based programs in the US, which involved participatory arts such as drama, photography, and dance, provided preliminary evidence that they reduced reportedly antisocial or criminalized behavior (Clawson & Coolbaugh, 2001 ). In these arts programs, adolescents may gain opportunities to improve their communication skills, self-confidence (Hughes, 2005 ), problem-solving skills, sense of purpose and autonomy, and social competence (Grigorenko, 2020 ), as well as finding new ways for positive self-expression (Gussak & Ploumis-Devick, 2004 ). The arts may thus have an important role in changing the individual, institutional, and social circumstances that can lead to reportedly antisocial or criminalized behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the occasion of a group of learners with learning difficulties and academic strengths or talents, the term was introduced to “twice exceptional” students who have coexisting diagnoses of both Special Educational Needs and who have been officially recognized as gifted/talented. As with the concept of giftedness, the double exception condition also puzzled researchers as to how it should be defined [ 164 , 165 ]. One of the definitions that received substantial consensus among twenty-six organizations supporting the research and educational needs of this population was proposed by Baldwin et al [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most seen overlap and confluence in the US is that of Specific Learning Disabilities (SLD), which focuses primarily on the significant discrepancy between a student’s level of ability and their academic performance [ 167 ]. However, more recent studies revealed that these co-occurrences of gifts/talents and disorders are not limited to a specific neurodevelopmental–intellectual disorder (e.g., ASD and SLD) but are phenomena recorded across the broader spectrum of developmental disabilities [ 165 , 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study of minorities within a single society necessarily engages additional issues, many of the concerns in this literature are similar to those found in more traditional cross‐cultural work, including researchers’ typical reliance on “etic” measures developed in other settings that fail to capture local meanings. In a recent issue of New Directions for Child and Adolescent Development , Grigorenko (2020a) and her colleagues tackle the problem of underrepresentation of diverse groups in the research literature from a broader point of view, by including children raised in orphanages (e.g., An, Zhukova, Ovchinnikova, & Grigorenko, 2020), American Indians and Alaska Natives (Garcia, 2020), HIV‐affected children (Tan, 2020), and “twice exceptional” children who are both talented and have behavioral disorders (Grigorenko, 2020b). In her commentary, Linda Jarvin proposes that understanding individual differences—within a wide range of sociocultural contexts—is “the necessary starting point to understand human development and functioning” (p. 159).…”
Section: Cultural Diversitymentioning
confidence: 99%